Uji aktivitas antibakteri ekstrak daun mayana jantan (Coleus atropurpureus Benth) terhadap pertumbuhan bakteri Streptococcus Sp. dan Pseudomonas Sp. - Muljono, Patrick; ., Fatimawali; Manampiring, Aaltje E. (Universitas Sam Ratulangi, 2016)
Abstract: The painted nettle (Coleus atropurpureus benth) is a plant that is known to have medicinal properties, especially the leaf. The active compounds that are contained in the leafs are thought to work as an antibacterial. This study aims to measure the inhibitory strength of painted nettle leaf (Coleus atropurpureus benth) extract against the growth of Streptococcus sp. and Pseudomonas sp. This was an experimental laboratory study. The polar extract of painted nettle leaf (Coleus atropurpureus benth) was tested by well method with concentrations of 100%, 80%, 60%, 40% and 20%. The polar extract of painted nettle leaf (Coleus atropurpureus benth) is the result of extraction of painted nettle that has been dried and then macerated using ethanol as the polar solvent. Tests were conducted to observe whether there is a zone of inhibition of polar extract of the painted nettle leaf (Coleus atropurpureus benth) against Streptococcus sp. and Pseudomonas sp. after 24 hours of incubation. Results show that the polar extract of painted nettle leaf (Coleus atropurpureus benth) with concentrations of 100%, 80%, 60%, 40% and 20% are able to inhibit the growth of Streptococcus sp. with an average of each concentration 12.8mm, 11.17mm, 8.67mm, 3.17mm and 2mm respectively while against Pseudomonas sp. with a mean diameter of each inhibition zone is 12.17mm, 10.67mm, 9.5mm, 7.17 and 5.17mm respectively. Conclusion: The polar extract of painted nettle leaf (Coleus atropurpureus benth) has an inhibitory effect against the growth of Streptococcus sp. and Pseudomonas sp.Keywords: coleus atropurpureus benth, inhibition, streptococcus sp,pseudomonas sp.Abstrak: Tumbuhan mayana jantan (Coleus atropurpureus benth) merupakan salah satu tanaman yang dikenal berkhasiat sebagai obat terutama bagian daunnya, senyawa aktif yang terkandung dalam daun mayana jantan mampu bekerja sebagai antibakteri. Penelitian ini bertujuan untuk mengukur dan mengetahui ada tidaknya daya hambat ekstrak daun mayana jantan (Coleus atropurpureus benth) terhadap pertumbuhan bakteri Streptococcus sp. dan Pseudomonas sp. Jenis penelitian yang digunakan adalah eksperimental laboratorik. Kadar ekstrak polar mayana jantan (Coleus atropurpureus benth) yang diujikan dengan metode sumuran adalah 100%, 80%, 60%, 40% dan 20%. Ekstrak polar daun mayana jantan (Coleus atropurpureus benth) merupakan hasil ekstraksi daun mayana jantan yang telah dikeringkan lalu dimaserasi menggunakan pelarut polar etanol. Uji dilakukan untuk mengamati ada tidaknya zona hambat dari ekstrak polar daun mayana jantan (Coleus atropurpureus benth) terhadap bakteri Streptococcus sp. dan Pseudomonas sp. setelah 24 jam inkubasi. Hasil penelitian menunjukkan ekstrak polar daun mayana jantan (Coleus atropurpureus benth) dengan konsentrasi 100%, 80%, 60%, 40% dan 20% dapat menghambat pertumbuhan bakteri Streptococcus sp. dengan rerata masing-masing yaitu 12,8mm, 11,17mm, 8,67mm, 3,17mm dan 2mm sedangkan Pseudomonas sp dengan masing-masing rerata diameter zona hambat yaitu 12,17mm, 10,67mm, 9,5mm, 7,17 dan 5,17mm. Simpulan: Ekstrak polar daun mayana jantan (Coleus atropurpureus benth) mempunyai daya hambat terhadap pertumbuhan bakteri Streptococcus sp. dan Pseudomonas sp.Kata kunci: coleus atropurpureus benth, daya hambat, streptococcus sp,pseudomonas sp.